2023
DOI: 10.33692/avrasyad.1167352
|View full text |Cite
|
Sign up to set email alerts
|

Otizmli Bireylere Yönelik Toplumsal Farkındalık Düzeyinin İncelenmesi

Abstract: Otizmli bireylerin toplum içindeki yerini anlamak için öncelikle toplumun otizme yönelik tutum ve bakış açısının açığa çıkarmak önem taşımaktadır. Toplum içinde otizmli bireyler sosyal iletişimde yaşadıkları sorunlar ve stereotipik hareketleri nedeni ile etiketlenme ve damgalamaya maruz kalabilmektedir. Toplumun olumsuz tutum ve davranışları ile sosyal hayat otizmli birey ve aileleri için zorluk oluşturabilmektedir. Toplumun otizmli birey ve aileye yönelik olumsuz tutum ve davranışları sonucunda, aile üyeleri … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
3
1
Order By: Relevance
“…The participants stated the most appropriate definition for autism as social interaction problem which is similar to the literature (Karabekiroğlu et al, 2009). However, the frequency of those describing autism as 'a kind of mental retardation' is higher than in previous studies ( Arslan, 2023;Karabekiroğlu et al, 2009).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The participants stated the most appropriate definition for autism as social interaction problem which is similar to the literature (Karabekiroğlu et al, 2009). However, the frequency of those describing autism as 'a kind of mental retardation' is higher than in previous studies ( Arslan, 2023;Karabekiroğlu et al, 2009).…”
Section: Discussioncontrasting
confidence: 56%
“…There are many awareness studies about autism conducted with university students (Kostiukow et al, 2020;Rakap et al, 2016), health workers (Chansa-Kabali et al, 2019), teachers (Alobaid & Almogbel, 2022;Rakap et al, 2018), and the community (Alsehemi et al, 2017;Rakap et al, 2022;Wei et al, 2022). The autism awareness of parents of typically developing children was investigated in some community-based studies ( Arslan, 2023;Karabekiroğlu et al, 2009). In Arslan (2023) it was observed that the awareness of autism in parents was lower than in individuals who did not have children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, no significant relationship was found between whether or not there was a person diagnosed with autism in their families and relatives and their level of knowledge about autism spectrum disorder. Similarly, in a study conducted in Türkiye, it was determined that those who have relatives with autism do not show completely correct approaches about autism (Arslan, 2023 ). In the study of Töret et al, the knowledge level of those in their close circle with individuals diagnosed with autism was significantly higher (Töret et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%